2019
DOI: 10.3390/nu11071564
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Gastrointestinal Digestion and Colonic Fermentation of High Dietary Fiber and Antioxidant-Rich Mango (Mangifera indica L.) “Ataulfo”-Based Fruit Bars

Abstract: Mango (Mangifera indica L.) is a tropical fruit which is considered to be a source of dietary fiber (DF) and phenolic compounds (PCs). In this study, high DF mango-based fruit bars were developed from whole mango (peel and pulp). The bars were evaluated for their nutritional composition, the bioaccesibility of PCs during gastrointestinal digestion, and the PCs metabolites profile after in vitro colonic fermentation. The amount of DF in a 30 g portion of mango bars was 9.5 g, i.e., 35% of the recommended daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 73 publications
2
23
1
Order By: Relevance
“…In other research, the colonic fermentation of mango peel showed an increased abundance of Dorea and Blautia, both involved in complex carbohydrates digestion [8]. Dorea could be the principal acetic acid producer during colonic fermentation reported by Hernández-Maldonado et al [13]. Even, members of the Lachnospiraceae family have been reported as a responsible of C-glucoside mangiferin deglycosylation for the production of norathyriol [46,47].…”
Section: Changes Of Microbial Composition During Mango (Mangifera Indmentioning
confidence: 84%
See 4 more Smart Citations
“…In other research, the colonic fermentation of mango peel showed an increased abundance of Dorea and Blautia, both involved in complex carbohydrates digestion [8]. Dorea could be the principal acetic acid producer during colonic fermentation reported by Hernández-Maldonado et al [13]. Even, members of the Lachnospiraceae family have been reported as a responsible of C-glucoside mangiferin deglycosylation for the production of norathyriol [46,47].…”
Section: Changes Of Microbial Composition During Mango (Mangifera Indmentioning
confidence: 84%
“…Even, members of the Lachnospiraceae family have been reported as a responsible of C-glucoside mangiferin deglycosylation for the production of norathyriol [46,47]. Dorea is a microorganism belonging to Lachnospiraceae family and could be related with the mangiferin biotransformation reported by Hernández-Maldonado et al [13]. On the other hand, Faecalibacterium, Roseburia and Eubacterium genera are involved in the fermentation of pectin oligosaccharides [48] and they are the main butyrate producers via Butyryl-CoA in the colon [49].…”
Section: Changes Of Microbial Composition During Mango (Mangifera Indmentioning
confidence: 97%
See 3 more Smart Citations